The future of agency : between autonomy and heteronomy - Dahms, Harry F. (Current perspectives in social theory ;, 2025)
In this thought-provoking volume, leading scholars address the multifaceted concept of agency, dissecting its significance, applications, and challenges across various domains, and situate agency in changing socio-historical contexts in which individuals as members of larger groups try to reconcile guiding norms and values with the material conditions of their lives. From sociological analyses to political explorations, the chapters traverse a rich landscape of ideas. The volume's centerpiece (Part I) are two essays by lead authors Axel van den Berg, a prominent Canadian social theorist at McGill University in Montreal, and Emre Amasyalı, a sociologist at Institut Barcelona d'Estudis Internacionals (IBEI), along with responses by other prominent social theorists provide reactions to and assessments of the two pieces, with a reply to critics by the authors. The second and third parts do not address the concept of agency explicitly, but they do provide treatments of the larger context in which the phenomenon is situated. Part Two includes an analysis of the relevance of the category of social class via Erik Olin Wright's reception of Max Weber and a reconstruction of how the idea of a guaranteed minimum (or basic) income can be traced alongside the history of social theory, beginning with Hegel. Part Three reflect on political transformations that have manifested in the United States in recent years, which are having a bearing on the reality of agency, and on opportunities to create documentaries in order to relay social-theoretical ideas and concepts to larger audiences. The Future of Agency ignites intellectual curiosity, challenges assumptions, and redefines our understanding of human agency and its ever-evolving role in our complex world.